PENINGKATAN MINAT BELAJAR SISWA PADA MAPEL IPA MATERI SIKLUS MAKHLUK HIDUP MELALUI MEDIA DIORAMA KELAS 4 SDN 11 LIMBOTO BARAT - Salma R. Hibalu; Jhems Richard Hasan; Sitti Rahmawati Talango (DIRASATUL IBTIDAIYAH, 2025)
Abstract This study aims to increase students' interest in learning science subjects on the subject of the Cycle of Living Things through diorama media in grade 4 of SDN 11 Limboto Barat. This research is a classroom action research (CAR) which is carried out in 2 cycles, with each cycle including the stages of planning, implementation, observation, and reflection. The subjects of the study were 30 grade 4 students of SDN 11 Limboto Barat. Data were collected through observation and documentation, then analyzed using descriptive percentage formulas for teacher activities, student activities, and student learning interests. Significant improvements were seen from the results of each cycle: in cycle I, teacher performance reached 47.5% and student learning interest 73.34%. Then, there was an increase in cycle II, with teacher performance reaching 76.5% and student learning interest 90%. Based on these findings, it can be concluded that the use of diorama media is effective in increasing the learning interest of grade 4 students of SDN 11 Limboto Barat in the subject of science on the subject of the Cycle of Living Things.Keywords: Minat Belajar Siswa, Media Diorama, IPAAbstrak  Penelitian ini bertujuan untuk meningkatkan minat belajar siswa pada mapel IPA materi Siklus Makhluk Hidup melalui media diorama di kelas 4 SDN 11 Limboto Barat. Penelitian ini adalah penelitian tindakan kelas (PTK) ini dilaksanakan dalam 2 siklus, dengan setiap siklus meliputi tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah 30 siswa kelas 4 SDN 11 Limboto Barat. Data dikumpulkan melalui observasi dan dokumentasi, kemudian dianalisis menggunakan rumus deskriptif persentase untuk aktivitas guru, aktivitas siswa, dan minat belajar siswa. Peningkatan yang signifikan terlihat dari hasil tiap siklus: pada siklus I, kinerja guru mencapai 47,5% dan minat belajar siswa 73,34%. Kemudian, terjadi peningkatan pada siklus II, dengan kinerja guru mencapai 76,5% dan minat belajar siswa 90%. Berdasarkan temuan ini, dapat disimpulkan bahwa penggunaan media diorama efektif dalam meningkatkan minat belajar siswa kelas 4 SDN 11 Limboto Barat pada mata pelajaran IPA materi Siklus Makhluk Hidup.KataKunci:Student Learning Interest, Diorama Media, Science.